2000
DOI: 10.1101/gr.10.5.659
|View full text |Cite
|
Sign up to set email alerts
|

Null Mutation of PCLN-1/Claudin-16 Results in Bovine Chronic Interstitial Nephritis

Abstract: Inherited chronic renal diseases are associated with failures in glomerular filtration and tubular resorption. Such failures invariably result from defects in selective filtration and absorption in surface renal epithelium. Recently, we described an autosomal recessive chronic interstitial nephritis with diffuse zonal fibrosis (CINF) in cattle. Bovine CINF, characterized by increased blood urea nitrogen, creatinine, and urinary proteins, leads to lethality before puberty, usually within the first 6 months or y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
83
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 12 publications
1
83
1
Order By: Relevance
“…Interestingly, in contrast to FHHNC, decreases in serum Mg 2+ and Ca 2+ concentrations are not apparent in cattle with claudin-16 deficiency, while a reduction in renal reabsorption rate has been suggested for Mg 2+ [21]. This suggests that there is a compensatory system(s) for metabolism of these divalent cations in the absence of claudin-16 or that bovine claudin-16 may have functions in paracellular transport of Mg 2+ and Ca 2+ distinct from those of the human counterpart despite their high homology in amino acid sequences [9,20].…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…Interestingly, in contrast to FHHNC, decreases in serum Mg 2+ and Ca 2+ concentrations are not apparent in cattle with claudin-16 deficiency, while a reduction in renal reabsorption rate has been suggested for Mg 2+ [21]. This suggests that there is a compensatory system(s) for metabolism of these divalent cations in the absence of claudin-16 or that bovine claudin-16 may have functions in paracellular transport of Mg 2+ and Ca 2+ distinct from those of the human counterpart despite their high homology in amino acid sequences [9,20].…”
mentioning
confidence: 86%
“…Since FHHNC has been characterized by renal Mg 2+ and Ca 2+ wasting, claudin-16 is likely to form aqueous pores that function as the paracelluar pathway for Mg 2+ and Ca 2+ in claudin-based TJs [3,27]. A recent report by Hou et al [11] clearly demonstrated that claudin-16/ paracellin-1 modulated the ion selectivity of the TJ by selectively increasing the permeability of Na + with no effect on Cl -when transfected into LLC-PK1 epithelial cells, and suggested that a loss of claudin-16/paracellin-1 function in the TAL could lead to losing the lumen-positive potential as the driving force for the reabsorption of Mg 2+ .Claudin-16 is also responsible for renal tubular dysplasia with interstitial nephritis in Japanese black cattle [9,20]. This disease is inherited in an autosomal recessive mode and characterized by renal failure, growth retardation, and early death due to renal dysfunction with a high incidence.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…CL-16 deficiency was examined using the DNA-based tests developed by Hirano et al [4]. Renal dysplasia was diagnosed from pathological findings.…”
Section: Animalsmentioning
confidence: 99%